(untitled) (ІННОВАЦІЙНА ЕКОНОМІКА, 2021)
Клапків Ю.М., Свірський В.С., Щур Р.І. АНАЛІЗ СУЧАСНИХ ТЕНДЕНЦІЙ У СТРАХОВОМУ СЕГМЕНТІ ФІНАНСОВОГО РИНКУ УКРАЇНИ Мета. Аналіз стану страхового сектору України, виявлення основних проблем його розвитку в сучасних умовах та визначення напрямів вдосконалення функціонування ринку страхових послуг в Україні. Методика дослідження. Науковою та методологічною базою статті є наукові праці, монографії, матеріали фахових видань, ресурси Інтернет. Під час проведення досліджень використано методи аналізу та синтезу, системно-функціональний метод та метод компаративістики, за допомогою яких пояснено більшість сучасних тенденцій, явищ і процесів у страховій сфері. Результати дослідження. Розглянуто основні тенденції розвитку страхового сегменту фінансового ринку України протягом 2012‒2020 рр. Проаналізовано динаміку кількості страхових компаній, основні показники діяльності страховиків, структуру валових та чистих страхових премій вітчизняних страховиків, показників перестрахування. На основі проведеного аналізу визначено основні проблеми функціонування ринку страхових послуг України та сформульовано пропозиції щодо вдосконалення його розвитку. Наукова новизна результатів дослідження. Запропоновано комплексний підхід до аналізу стану ринку страхових послуг як важливої складової фінансового сектору економіки з більшістю властивих йому характеристик, функцій і принципів; економічного простору, в якому взаємодіють інституційні одиниці з реалізації послуг страхування; сукупності упорядкованих грошових потоків між суб’єктами у страховому сегменті фінансового ринку. Практична значущість результатів дослідження. Результати проведеного дослідження можуть стати підґрунтям подальших наукових досліджень для системного вирішення практичних проблем у даній сфері, розробки та вжиття заходів, спрямованих на досягнення прискореного поступального розвитку ринку страхових послуг для забезпечення соціально-економічного зростання. Ключові слова: страхування, страхові послуги, ринок страхових послуг. Klapkiv Y.M., Svirskyi V.S., Shchur R.I. THE ANALYSIS OF CURRENT TRENDS IN THE INSURANCE SEGMENT OF THE FINANCIAL MARKET OF UKRAINE Purpose. Analysis of the state of the insurance services market of Ukraine, identification of the main problems of its development in modern conditions and determination of directions for improving the functioning of the insurance services market in Ukraine. Methodology of research. The scientific and methodological basis for the article are scientific works, monographs, materials of professional publications, Internet resources. During the research the methods of analysis and synthesis, system-functional method and method of comparative studies were used, with the help of which most modern tendencies, phenomena and processes in the market of insurance services are explained. Findings. The article is devoted to current trends of the insurance in Ukraine. The study examines the main trends in its development during 2016-2020. The dynamics of the number of insurance companies, the main indicators of insurers, the structure of gross and net insurance premiums of domestic insurers, reinsurance indicators are analyzed. Based on a dataset of Ukrainian insurance industry, we analyse the impact of transformation of the insurance sector. Based on the analysis, the main problems of the insurance services market of Ukraine are identified and proposals for improving its development are formulated. The results illustrate major tasks the industry is facing: enhancing the customer experience, improving its business processes, offering new products, and preparing for competition with other industries, imperfection of regulatory regulation of the insurance sector; underdevelopment of the life insurance segment and other types of insurance (agricultural, environmental, catastrophic risks and life insurance, cyber risks); low solvency of potential consumers of insurance services, low level of capitalization of insurance companies, lack of insurance culture, distrust of the insurance institution; fraud and neglect of the rights of policyholders by some insurance companies; low financial literacy of policyholders. Moreover, we identify key areas of change of the insurance services market of Ukraine: creation of a centralized online database of insurance contracts; improving the system of taxation of insurance activity; adaptation of Ukrainian legislation in the field of insurance to EU legislation; introduction of high technologies in insurance services; improvement of marketing management; creation of an export insurance system by establishing a special organization for export insurance and financing; introduction of insurance culture and traditions. Originality. A comprehensive approach to the analysis of the state of the insurance market as an important component of the financial sector of the economy with most of its inherent characteristics, functions and principles; economic space in which institutional units for the implementation of insurance services interact; a set of orderly cash flows between the subjects of the insurance market. Practical value. The results of the study can be the basis for further research to systematically address practical problems in this area, development and implementation of measures aimed to achieve accelerated progressive development of the insurance market to ensure socio-economic growth. Key words: insurance, insurance services, insurance services market.